1976
DOI: 10.1007/bf02636812
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer and scale‐up in fat hydrogenation

Abstract: The mass transfer of hydrogen in fat hydrogenation was studied in two geometrically similar reactors of 30 and 500 liter capacity equipped for hydrogen rec/rculation. A scale-up rule was formulated on the basis of the experiments and checked in industrial hydrogenations with a 24 m 3 reactor. The scale-up rule found was similar to the equal mixing time rule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…For different stirrer speeds, k~a B values were also evaluated. On comparison of these values with the predictions of literature correlations (such as Bern et al, 1976, andYagi andandYoshida, 1975), it is observed that the values obtained in this work are lower. This can be explained on the different hydrodynamic conditions encountered in the reactor used.…”
Section: Comparison Of Experimental and Predicted Resultssupporting
confidence: 66%
“…For different stirrer speeds, k~a B values were also evaluated. On comparison of these values with the predictions of literature correlations (such as Bern et al, 1976, andYagi andandYoshida, 1975), it is observed that the values obtained in this work are lower. This can be explained on the different hydrodynamic conditions encountered in the reactor used.…”
Section: Comparison Of Experimental and Predicted Resultssupporting
confidence: 66%
“…As can be seen in ref. (9), a satisfactory model for the rapeseed oil hydrogenation reactions was computed using the algorithm.…”
Section: Illustration Of the Computational Methods On The Fat Hydrogenmentioning
confidence: 99%
“…Moreover, the hydrogen solubility constant was found to be K H --0.0203 exp(-710/T) mol/liter arm. (9), where T is the absolute temperature in Kelvin. The number 0.039 in eq.…”
Section: Influence Of the Mass Transfer Stepsmentioning
confidence: 99%
“…Although many investigations have been carried out on this subject, setting up of general rules for correlating the k l a l value with agitation and hydrogen gassing parameters, and estimating the overall hydrogenation rate in gas-liquid-solid reactor design, often lead to contradictory results and seem impossible [187]. Although many investigations have been carried out on this subject, setting up of general rules for correlating the k l a l value with agitation and hydrogen gassing parameters, and estimating the overall hydrogenation rate in gas-liquid-solid reactor design, often lead to contradictory results and seem impossible [187].…”
Section: Mass Transfer Resistance Inverse Resistance Termmentioning
confidence: 99%